Challenges and strategies of implementing clinical librarianship: A case study of hospitals of Tehran metropolis - Dinpajuh, Zahra; Mohaghegh, Niloofar; Zarghani, Maryam; Khazaee-Pool, Maryam; Ghamgosar, Arezoo; Khani, Sedegheh (Malaysian Journal of Library and Information Science, 2024)
Rapid changes in most treatment fields and evidence-based medical trends emphasize the role of clinical librarian in providing information services to treatment teams. The new task of librarians in treatment teams has faced barriers and challenges. The current study was conducted to assess the obstacles and offer solutions for the implementation of the role of clinical librarian in Iranian hospitals. This qualitative study was conducted on 15 librarians with experience in work and research related to presenting information services to the treatment team. The librarians were interviewed using purposive, available sampling method. The data collection tool was a semi-structured interview, which continued until data saturation, and data analysis was done using thematic analysis method. A total of 147 initial codes, 122 main codes, and 35 subcategories were extracted from analysis of 15 interviews. After detailed evaluation and integration of the subcategories, ten categories and two main themes were determined. The main barriers are related to the lack of support from executive organizations, the absence of appropriate training programs, and the shortage of skills to enter the treatment teams. These barriers have prevented the approval of clinical librarian as an independent job position. The mentioned strategies are dependent on the support of executive organizations in two sectors: Ministry of Health and hospitals in creating job titles and feeling the need for information specialists in medical teams, as well as universities in defining official and independent disciplines by developing appropriate educational programs and attracting qualified people.